Innovative Approaches in the Design of Flavonoid-Based Functional Foods for Pediatric Nutrition - María Paula Deaza-Fernández; Daniela Sarmiento-Soto; Maria Ximena Quintanilla-Carvajal (Applied Food Research)
This review presents a novel and application-oriented framework for the development of flavonoid-rich functional foods aimed at mitigating the adverse effects of chemo- and radiotherapy (particularly mucositis) in pediatric cancer patients. Uniquely, it compiles all critical scientific, technological, and regulatory elements needed to create functional food products that are not only therapeutically effective and safe, but also sensorially appealing and commercially viable. The review covers flavonoid classification, their bioactive properties, (especially antioxidant and anti-inflammatory effect), and the relevant regulatory landscape. It also details methodologies for assessing functionality, including in vitro, in vivo, and in silico approaches, and explores enabling technologies such as encapsulation and colloidal systems to improve bioavailability and product stability. Notably, evidence from most studies indicates a marked reduction in chronic mucositis to moderate or mild levels within seven days of product use, highlighting the clinical potential of these formulations. By addressing both health efficacy and market readiness, this review serves as a practical and integrative guide for researchers and food developers. It advocates for interdisciplinary collaboration to translate scientific insights into real-world, consumer-ready solutions that improve nutritional support and quality of life for children undergoing cancer treatment.